On a Regular Hypersimplex Inscribed into the Multidimensional Cube - Medianik, A. I. (Журнал математичної фізики, аналізу, геометрії, 2006)
It is proved the existence of a regular hypersimplex inscribed into the (4n-1)-dimensional cube under the vanishing condition of the resultant of some system of 4n-1 algebraic equations with 4n-1 unknown quantities. Mathematics Subject Classification: 52B, 05B20.